The Taming of the Skew: Facts On Canada’s Energy Trade - Trevor Tombe (The School of Public Policy Publications, 2014)
Public perception of Canada’s energy trade is skewed towards Alberta’s oilsands and pipeline projects; a look at the facts reveals a more complex picture. Over the last decade, growth in Canada’s energy trade has been nothing short of historic. Energy exports have become so significant that the revenue is now equivalent to nearly $9,000 for every Canadian household. And it is only projected to grow much, much larger. While Western Canada leads the industry, every region — including Ontario, Quebec and Atlantic Canada — plays a key role. Today, nearly every province is a net energy exporter. The energy sector also adds much to Canada’s economy, with valueadded and productivity higher than nearly every other sector. When it comes to labour compensation, oil and gas extraction is the highest-paying sector in the country, at more than three times the average hourly earnings in the Canadian economy generally, and nearly 50 per cent higher than manufacturing. It is vital that policy debates rely on accurate information; unfortunately, this is not always the case. The often heated rhetoric neglects important aspects of Canada’s energy trade. For example, the type of energy that Canada trades has undergone a dramatic transformation. Ten years ago, natural gas was the largest energy export but today accounts for less than one-tenth of the total. Meanwhile, crude oil exports have more than quadrupled. Even more surprising to many Canadians, and perhaps even policy-makers, is how much energy Canada imports. Even Alberta, with its vast energy reserves, imports a considerable amount of energy. Alberta’s energy imports have grown faster than any other province and will soon exceed Ontario’s, a province more than three times larger with very little of its own oil production. Trade in energy is also intimately tied with Canada’s foreign investment policies. The majority of Canada’s energy trade is in the form of related-party transactions. For example, Suncor exports oil from its Canadian operations to its American refineries to supply its American gas stations. This fact has important implications for Canadian policy: foreign multinational firms are an important and growing part of the country’s rapidly expanding energy trade. Promoting Canada’s energy trade requires lowering investment barriers and creating a predictable and stable investment climate for foreign direct investment. Yet, in practice, Canada has recently shown a tendency for the opposite, with governments blocking the takeover of Potash Corporation by Australia’s BHP Billiton, and announcing, after the takeover of Nexen Inc. by a Chinese firm, that future takeovers would face even greater scrutiny. Foreign investment in Canada’s energy has already begun to fall, feasibly as a result of these increasingly hostile signals. Canada has a great deal riding on the future of its energy industry — an industry that is as economically beneficial as any other, if not more so. It is absolutely crucial that we ensure our energy-trade policies are based on high-quality and objective information; politicized and emotional rhetoric does not help.